The Starting Points of ‘Popular Music Studies’ in Czechoslovakia - Blüml, Jan (Załącznik Kulturoznawczy, 2020)
The story of the emergence of the field of Popular Music Studies is usually associated with the activities of Western researchers and historically set in the 1980s. Although the research conducted by academics from the Eastern communist countries – due to the tradition of Marxist scholarship – preceded that of their Western counterparts in certain respects, by years or even decades, it is rarely mentioned. This article examines the origins of the musicology of popular music as it was officially established in the early 1960s in communist Czechoslovakia.